Protective role of nitric oxide in ocular toxoplasmosis. Issue 7 (July 1996) - Hayashi, S.; Chan, C. C.; Gazzinelli, R. T.; Pham, N. T.; Cheung, M. K.; Roberge, F. G.
Abstract : AIMS: To evaluate the role of nitric oxide (NO) in ocular involvement during systemic toxoplasmosis. METHODS: C57B1/6 mice were infected with Toxoplasma gondii strain ME49. The synthesis of NO was inhibited by an intraperitoneal injection of aminoguanidine every 8 hours, starting on the day of infection. Control infected mice received phosphate buffered saline vehicle alone. After 14 days, the ocular lesions were evaluated by histopathological examination. The expression of NO synthase induced in the spleen by toxoplasma infection was evaluated by immunostaining. The production of NO by the spleen cells of infected mice was measured by the colorimetric assay of Griess in the supernatant of cultures stimulated with toxoplasma antigen or concanavalin A. RESULTS: The inhibition of NO production in T gondii infected mice resulted in a marked increase in the symptoms of ocular inflammation. We observed a strong induction of NO synthase expression in the spleen of infected animals. In culture, the spleen cells from these mice produced high levels of NO in response to T gondii antigens. This elevation of NO synthesis was suppressed in the presence of aminoguanidine. CONCLUSION: This study indicates that NO plays a crucial role in the protection against T gondii infection as reflected by the severity of the ocular involvement.